(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Immunological infertility remains a challenging diagnosis in reproductive medicine. Corticosteroids, as potent immunosuppressive agents, have been investigated for their role in reducing antisperm antibodies and improving fertility outcomes. In this study, 40 patients with confirmed immunological infertility were divided into two groups: 20 received corticosteroid therapy, while 20 were assigned to placebo. Treatment outcomes were compared in terms of pregnancy rates and improvement in reproductive parameters. Corticosteroids demonstrated measurable benefits in selected cases, though their use must be carefully balanced against potential adverse effects.